2011
DOI: 10.1097/pts.0b013e31820dbe02
|View full text |Cite
|
Sign up to set email alerts
|

Developing a High-Performance Team Training Framework for Internal Medicine Residents

Abstract: Teamwork principles can be adapted from other disciplines and applied to internal medicine. After a single session, residents displayed greater knowledge of teamwork principles and reported changed attitudes toward key teamwork behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 10 publications
1
51
0
1
Order By: Relevance
“…Zajano et al (2014) (15) reported that physical environment of the emergency department and staff's compatibility with this environment is important and Ajeigbe et al (2013) (22) also noted that the information required to perform daily activities; care and treatment of patients should be available to emergency workers. Carbo et al (2011) (23) found that emergency department staff should have sufficient knowledge of the physical environment to carry out daily activities and continually evaluate the environment in terms of critical information about the patient.…”
Section: Estimated Marginal Meansmentioning
confidence: 99%
“…Zajano et al (2014) (15) reported that physical environment of the emergency department and staff's compatibility with this environment is important and Ajeigbe et al (2013) (22) also noted that the information required to perform daily activities; care and treatment of patients should be available to emergency workers. Carbo et al (2011) (23) found that emergency department staff should have sufficient knowledge of the physical environment to carry out daily activities and continually evaluate the environment in terms of critical information about the patient.…”
Section: Estimated Marginal Meansmentioning
confidence: 99%
“…11 It is a mental model of the current state of an environment with three distinct levels: perception is simply the state of being aware of the environment, comprehension implies an understanding of the implications of that state, and projection is the ability to predict future events from that understanding. 11 It is a mental model of the current state of an environment with three distinct levels: perception is simply the state of being aware of the environment, comprehension implies an understanding of the implications of that state, and projection is the ability to predict future events from that understanding.…”
Section: Situational Awarenessmentioning
confidence: 99%
“…, Carbo et al . ) and TEAMStepps (Team Strategies and Tools to Enhance Performance and Patient Safety, e.g. Alonso et al .…”
Section: Introductionmentioning
confidence: 99%